Comparison between two swing-up algorithms: partial feedback linear and energy based method - Hong , Gia Bao; Le, Thi Thanh Hoang; Nguyen, Minh Tam; Vu , Dinh Dat; Nguyen, Van Dong Hai (Journal of Technical Education Science, 2019)
Beside the balancing algorithms, swing-up is also an important problem in controlling under-actuated system. Swing-up is necessary to move automatically system to a suitable position for others balancing controls to operate. However, a limited number of researches has been focused on this problem. In this paper, the authors compare two swing-up algorithms from other researches: partial feedback linear and energy-based methods in both simulation and experiment. In previous studies, these methods were presented in only a mathematical description and simulation. Moreover, no comparison was concerned between these methods. Thence, experimental results from this paper implement more descriptions in a real-time system. Our both simulation and experiment results prove that recent energy-based method gives better controlling response than classical partial feedback linear method under external force. In this research, pendubot, a popular model in control engineering, is an under-actuated object.